Effects of deposited Pt particles on the reducibility of CeO2(111) - Bruix, Albert; Migani, Annapaola; Vayssilov, Georgi N.; Neyman, Konstantin M.; Libuda, Jörg; Illas, Francesc (Physical Chemistry Chemical Physics, 2011)
The interaction of Pt particles with the regular CeO2(111) surface has been studied using Pt-8 clusters as representative examples. The atomic and electronic structure of the resulting model systems have been obtained through periodic spin-polarized density functional calculations using the PW91 exchange-correlation potential corrected with the inclusion of a Hubbard U parameter. The focus is on the effect of the metal-support interaction on the surface reducibility of ceria. Several initial geometries and orientations of Pt-8 with respect to the ceria substrate have been explored. It has been found that deposition of Pt-8 over the ceria surface results in spontaneous oxidation of the supported particle with a concomitant reduction of up to two Ce4+ cations to Ce3+. Oxygen vacancy formation on the CeO2(111) surface and oxygen spillover to the adsorbed particle have also been considered. The presence of the supported Pt-8 particles has a rather small effect (similar to 0.2 eV) on the O vacancy formation energy. However, it is predicted that the spillover of atomic oxygen from the substrate to the metal particle greatly facilitates the formation of oxygen vacancies: the calculated energy required to transfer an oxygen atom from the CeO2(111) surface to the supported Pt-8 particle is only 1.00 eV, i.e. considerably smaller than 2.25 eV necessary to form an oxygen vacancy on the bare regular ceria surface. This strongly suggests that the propensity of ceria systems to store and release oxygen is directly affected by the presence of supported Pt particles.